1979
DOI: 10.1037/h0077579
|View full text |Cite
|
Sign up to set email alerts
|

Memory deficits associated with senescence: A neurophysiological and behavioral study in the rat.

Abstract: Neurophysiological and behavioral measures were obtained from 32 senescent (28-34 mo) and 32 mature adult (10-16 mo) rats. Extracellularly recorded synaptic responses were obtained from electrodes chronically implanted in the fascia dentata and perforant path. The rats were first tested on a circular platform, which favored the use of spatial cues for its solution, and the senescent rats were shown to exhibit poorer memory for the rewarded place. When granule cell synaptic responses were recorded after a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
840
5
17

Year Published

1996
1996
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 1,871 publications
(937 citation statements)
references
References 61 publications
41
840
5
17
Order By: Relevance
“…Our results are consistent with data obtained from studies performed in the aged rabbit (Solomon and Pendlebury, 1992) and rat DG under similar experimental conditions (Barnes, 1979;De Toledo-Morrell and Morrell, 1985) and suggest that aging affects NMDA receptordependent LTP maintenance at different hippocampal synapses in a homogeneous fashion. Given that previous studies have reported impaired DG LTP duration in aged rats (Barnes, 1979) and that the CA3 region receives MPP inputs from the same layer II stellate cells in the entorhinal cortex that project to the DG (Tamamaki and Nojyo, 1993), it may be that the agerelated deficits in LTP duration in the DG and area CA3 share common mechanisms. Reduced CA3 neuron number is unlikely to play a role in the impaired MPP-CA3 LTP duration observed here in aged rats because recent evidence indicates that neuron density in the CA3 pyramidal cell layer remains constant in aged rats (Poe et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our results are consistent with data obtained from studies performed in the aged rabbit (Solomon and Pendlebury, 1992) and rat DG under similar experimental conditions (Barnes, 1979;De Toledo-Morrell and Morrell, 1985) and suggest that aging affects NMDA receptordependent LTP maintenance at different hippocampal synapses in a homogeneous fashion. Given that previous studies have reported impaired DG LTP duration in aged rats (Barnes, 1979) and that the CA3 region receives MPP inputs from the same layer II stellate cells in the entorhinal cortex that project to the DG (Tamamaki and Nojyo, 1993), it may be that the agerelated deficits in LTP duration in the DG and area CA3 share common mechanisms. Reduced CA3 neuron number is unlikely to play a role in the impaired MPP-CA3 LTP duration observed here in aged rats because recent evidence indicates that neuron density in the CA3 pyramidal cell layer remains constant in aged rats (Poe et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…As is the case at the MPP-DG synapse (Bramham et al, 1991), LTP induction at the MPP-CA3 synapse is dependent on NMDA receptor activation current data). Consistent with data obtained in the aged rat DG (Barnes, 1979) and area CA1 (Barnes et al, 1996), our finding that the same magnitude of MPP-CA3 LTP can be induced in aged rats as in young rats after the same number of identical high-frequency stimulation sessions suggests that NMDA receptor-mediated processes are intact in aged rats at this synapse. This observation does not exclude the possibility that individual NMDA receptor-mediated MPP-CA3 synaptic responses are reduced in aged rats, as is the case at the MPP-DG synapse .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations